Cardiovascular response to resistive and non resistive reciprocal pulley exercise among apparently healthy subjects - A A Amaeze; N O Egbo; C I Ezema (International Journal of Medicine and Health Development, 2011)
Background: Reciprocal pulley exercise is usually recommended for physiotherapy patients undergoing rehabilitation for muscle strengthening exercises or improvement in joint range of motion but, very little is known of its effects on the cardiovascular system. Aims: This study aimed at investigating the blood pressure and pulse rate response to resistive and nonresistive pulley exercises among apparently healthy subjects. Methods: This is an experimental study involving a pretest-posttest randomized groups design. Eighty apparently healthy subjects from the age of 18 to 25 participated in the study. Their informed consent and the hospital ethical approval were duly obtained. They were grouped into two: group A carried out resisted reciprocal pulley exercise while group B carried out free reciprocal pulley exercise, for 50 repetitions while sustaining each stretching for 5 seconds. Their blood pressure and pulse rate was measured before and immediately after the exercises. The data was analysed using t-test. Results: The results showed that the group A subjects recorded a significant increase in systolic BP (p =0.015) and pulse rate (p = 0.0034) but no significant increase in diastolic BP (p = 0.204). The group B subjects recorded significant increase in pulse rate (p= 0.005), systolic (p = 0.035) and diastolic BP (p= 0.003). Conclusion: It is concluded that reciprocal pulley exercise may have significant changes in blood pressure and pulse rate.